Gabby Reiland: capstone - Reiland, Gabby, artist (Colorado State University. Libraries, 2025)
The artist's statement: Gabby Reiland is an artist interested in the intersection of the visual arts and storytelling. With an electronic art major and creative writing minor, she explores both creative mediums separately and in tandem with each other. She is excited by every medium that combines the two, whether that is through animation, storybooks, comics, or games. She also has worked with a variety of physical mediums such as laser cutting and printmaking. Her work often features animals and fictional creatures and utilizes their symbolism or their separation from reality for her works. She has two short stories published in The Greyrock Review. Her short story "The Pessimist Eats an Orange" explores themes of connection and satisfaction through fruit imagery while "Fowl Worship" explores belonging and the natural world with a fantasy twist. She first dipped her toes into game development with "Wyrmbel", a short game with branching options. She is currently working on a new game called "Washing Bears Turn to Machines". She hopes to continue to create games, animations, and tell stories. --------- Washing Bears Turn to Machines is a visual novel that explores communication and the rising prominence of technology. It features 2D animated portraits and interactivity based on player choices during conversations. The title 'Washing Bears Turn to Machines' is a language pun. In several languages raccoons have a name that is some variation of 'washing bear' or 'washing rat' such as orsetto lavatore in Italian, raton laveur in French, or waschbär in German. All of the characters, except for the two raccoon dogs, are animals within the raccoon family procyonidae. In the demo version of the game, I established a workflow that I can apply to future projects. I worked on this project in both my experimental video and interactive media classes so I could dive deep into this project. I worked on animations and the script throughout the semester then dove into furthering my understanding of code. Understanding each element of the game helped me combine them and make specific creative decisions. By making the demo, I developed a better understanding of the characters and the questions I want to explore in the full story, such as how do we communicate with each other between barriers in language, age, and space? With people being tempted to use AI to write emails, essays, or translate text, how do we get people to value genuine conversation and thought? With phones and the internet, many of our conversations are filtered through a layer of technology. This opens up the opportunity to connect with people across vast distances, but it also means keeping in contact with people has become dependent on text, email, and phone calls. In addition, how do we turn to fantasy and sci-fi stories in modern times to process or turn away from our current reality, especially when looking at dystopian sci-fi stories or idyllic fantasy worlds?
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art